Sensibilidade da enzima acetilcolinesterase (e.c. 3.1.1.7) à nicotina in vitro e in vivo - Figueiró, Micheli (2005)
This work valued the sensibility of the acetylcholinesterase from different sources and brain regions at nicotine in vitro, and the effects of the acute and subchronic exposures at the alkaloid on the brain acetylcholinesterase and serum cholinesterase activities, body weight gain and cerebral weight of female rats. The activity of cholinesterases was determined by spectrophotometric method of Ellman (1961), using acetylthiocholine as substrate. In the nicotine in vitro study, the enzymatic analysis was performed with nicotine concentrations ranging from 0 to 1 mM and substrate concentration of 0 -1 mM. In the ex vivo enzymatic assay, 0.8 mM of acetyltiocholine was used. The results regarding at the effects of the nicotine in vitro demonstrated that the enzyme activity from rat brain, human blood and purified of Electric Eel was competitively inhibited by lower nicotine concentrations. The similar effect may be due to the predominance of the G4 molecular globular form in these three sources. The acetylcholinesterase activity from brain structures: cortex, striatum, hippocampus, hypothalamus and cerebellum, was inhibited by nicotine. Considering the IC50, the inhibitory effect was similar among the structures, although the striatum and cortex enzyme seems to be more sensitive, whereas the hypothalamus seems to be less sensitive to alkaloid. The kinetics constants calculated by Michaelis-Menten methods for striatum, cortex and hypothalamus demonstrated that the nicotine induce an increase of Km and a decrease of Vmax. These results showed that the increase of the substrate concentration was not enough for to reach the original Vmax (absence of inhibitor), even in the presence of the low nicotine concentrations. The effects of ex vivo nicotine exposure were investigated after acute or subchronic alkaloid administration. Female Wistar rats with 30 days old received one dose of 0, 0.5, 1 or 5 mg/kg (i.p.) of nicotine (acute exposure) and 10 minutes later were anesthetized and killed by decapitation. Brain was removed and homogenized, the blood was colleted and both centrifuged for obtain the S1 fraction and serum, respectively. In the subchronic exposure, female Wistar rats of 30 days old received doses of 0, 0.5 or 1.0 mg/kg (s.c.) of nicotine for 15 or 30 days, administered twice a day (0, 1 or 2 mg/kg/day). The animals were weighed every two days and killed 12 h after the last injection. The brain and the blood were prepared as previously described. The results demonstrated that the cerebral AChE and serum ChE activities were not changed by acute or subchronic exposure (15 or 30 days) at nicotine. The body weight gain and the cerebral weight also were not altered by alkaloid exposure. The absence of effect on the enzymatic activities ex vivo may be related at least the two possibilities: low levels of nicotine reached in vivo; or a possible enzymatic inhibition present in vivo induced by treatments but not apparent due to substrate excess assayed ex vivo, since the in vitro inhibitory effect of the nicotine on the AChE presents an competitive component.